1974
DOI: 10.3750/aip1974.04.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Experimental methemoglobinemia in rainbow trout

Abstract: Institute of IchthyologyIn the experimental way methemoglobinemia was caused to occur in rainbow trout, Salmo gairdneri Rich., 1836 by keeping the fishes for 11 weeks in Ca(N0 3 ) 2 and KN0 3 solutions, the N0 3 doses in which being 26.2 mg/1 and 30.6 mg/1, respectively.At the ·same time measurements of the hepatic tissue respiration rate, histopathologic studies of liver as well as examination of the peripheral blood and hematopoietic organs were carried out.Marked changes which eventually could be lethal wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 1 publication
0
15
0
1
Order By: Relevance
“…Brownell (1980), reported 24 h LCs0 levels ranging from 18.8 to 38.3 g N O 3 1-1 for several species of marine fish, and ECs0 levels ranging from 2.6 to 4.5 g NO;-1-1. The only indication that rela- tively low concentrations of nitrate may be harmful to fish comes from Grabda et al (1974), who found that rainbow trout exposed to 22.0-26.4 mg N O f 1-1 displayed increased blood levels of ferrihaemoglobin, damage to the peripheral blood and haematopoietic centres, and liver damage. However, their data was not definitive since nitrite was not measured in the experiments, and these effects may have been caused by nitrite accumulation (Colt and Armstrong 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Brownell (1980), reported 24 h LCs0 levels ranging from 18.8 to 38.3 g N O 3 1-1 for several species of marine fish, and ECs0 levels ranging from 2.6 to 4.5 g NO;-1-1. The only indication that rela- tively low concentrations of nitrate may be harmful to fish comes from Grabda et al (1974), who found that rainbow trout exposed to 22.0-26.4 mg N O f 1-1 displayed increased blood levels of ferrihaemoglobin, damage to the peripheral blood and haematopoietic centres, and liver damage. However, their data was not definitive since nitrite was not measured in the experiments, and these effects may have been caused by nitrite accumulation (Colt and Armstrong 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Branchionecrosis A considerable reduction in the erythrocyte count and erythrocyte cytolysis were found to accompap.y the acute fonn of the disease. Cytolysis has been known as one of the effects of toxic agents (Waluga and Flis, 1971;Grabda et al, 1974;Schreckenbach and Spangenberg, -1978). Recent findings on adverse effects of ammonia as a direct branchionecrosis-causing factor seem to be corroborated by such morphological changes in erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, hematologic assays allow to estimate the force of a disease-causing agent (Einszporn-Orecka and Wierzbicka;1974;Grabda et al, 1974); on the other, they can be very helpful in identifying the disease and in diagnosing conditions of unclear etiology (Lejman, 19 5 5;Spoljanskaja, 1966;Blaxhall and Daisley, 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The most toxic effect of nitrate on aquatic environment is the eutrophication [6]. Moreover, the discharge of these nitrogenous compounds into the aquatic environment can also cause serious problems such as the transformation of oxygen-carrying pigments (e.g., hemocyanin and hemoglobin) to a form of methemoglobin which is incapable of carrying oxygen [7][8][9]. Conventional physicochemical and biological treatment processes for denitrification of wastewater including reverse osmosis, ion-exchange, adsorption, chemical coagulation and bacterial assimilation do not provide long-term solutions due to several limitations and drawbacks such as involvement of complicated procedures, tendency to generate concentrated wastes and high cost [10].…”
Section: Introductionmentioning
confidence: 99%